1994
DOI: 10.1111/j.1365-4362.1994.tb01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Azelastin on Pruritus and Plasma Histamine Levels in Hemodialysis Patients

Abstract: The present data do not support the thesis that the increased plasma histamine concentration is causally related to pruritus in hemodialysis patients or that the antiallergic drug, azelastin HCL, alleviates the pruritus of dialysis patients by decreasing plasma histamine levels. The possible role of the increased tissue levels of histamine remains to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The application of leukotriene B 4 to skin induces itching, whereas prostaglandin E 2 , another arachidonic acid metabolite synthesized by cycloxygenase, does not (Andoh and Kuraishi, 1998). The induction of itching by leukotriene B 4 is thought to be mediated primarily by its receptor in sensory neurons, because blockers of leukotriene B 4 receptors alleviate the itching of dermatitic skin or leukotriene B 4 -induced scratches (Matsui et al, 1994;Kanai et al, 1995). However, some proportion of the itching induced by leukotriene B 4 is attributable to receptorindependent mechanisms in sensory neurons (Andoh and Kuraishi, 1998), which may include the direct action of leukotriene B 4 on TRPV1 in sensory neurons because of its agonistic activity on TRPV1 (Hwang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The application of leukotriene B 4 to skin induces itching, whereas prostaglandin E 2 , another arachidonic acid metabolite synthesized by cycloxygenase, does not (Andoh and Kuraishi, 1998). The induction of itching by leukotriene B 4 is thought to be mediated primarily by its receptor in sensory neurons, because blockers of leukotriene B 4 receptors alleviate the itching of dermatitic skin or leukotriene B 4 -induced scratches (Matsui et al, 1994;Kanai et al, 1995). However, some proportion of the itching induced by leukotriene B 4 is attributable to receptorindependent mechanisms in sensory neurons (Andoh and Kuraishi, 1998), which may include the direct action of leukotriene B 4 on TRPV1 in sensory neurons because of its agonistic activity on TRPV1 (Hwang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…One study suggested increased sensitivity to histamine in uremic patients with pruritus [17]. However, the majority of studies were not able to demonstrate any correlation between an increased plasma histamine level and uremic pruritus [14,36,38,39]. Since antihistamines are not usually effective for treating uremic itch [2], the role of histamine is likely not significant in uremic pruritus.…”
Section: Mast Cells and Autacoidsmentioning
confidence: 99%
“…2,[77][78][79] Because of the potential for dangerous side effects related to over-sedation, especially in the elderly, these medications cannot be recommended as first line for the treatment of CKD-aP.…”
Section: Antihistamine Treatmentmentioning
confidence: 99%